Analisis Kepentingan Stakeholder dalam Pengelolaan UB Forest berbasis Hutan Pendidikan untuk Mendukung Keberlanjutan Sistem Agroforestri - Sentanu, I Gede Eko Putra Sri; Kumalasari, Klara (FKIP Universitas Wisnuwardhana, 2020)
The purposes of this study are to understand the history and management of the Agroforestry system in UB Forest, especially during the transition from forestry to UB management; to understand the issues related to Agroforestry policies and regulations from the central/local government and its consequences on the management of UB Forest; to identify the main stakeholders and stakeholders in the management of UB Forest, their roles, perceptions, interests, and networks that have the potential to influence their involvement in the Agroforestry system; to identify existing social conflicts and potential future conflicts among stakeholders that may occur due to competing interests, issues of justice, legal issues and cultural issues related to agroforestry development in UB Forest; and developing a collaborative governance model to support sustainable agroforestry in UB Forest. This study used Case Study Research. Data collection techniques are interviews, observation, and documentation. The analysis technique of this research uses the Mcnabb technique. The results showed that collaborative government supported the sustainability of the agroforestry system in UB forest management by involving many stakeholders, such as context setters: local communities, student involvement. crowed: farmers, key players: UB forest management, subjects: the role of the Institutions of Forest Village Community, and The Forest Farmer Groups. However, UB forest management has not involved the community optimally, of course, this is a consideration by UB forest management so that it can involve local communities in supporting the involvement of the agroforestry system.